Application of DKI and IVIM imaging in evaluating histologic grades and clinical stages of clear cell renal cell carcinoma - Cheng, QiChao; Ren, AnLi; Xu, XingHua; Meng, Zhao; Feng, Xue; Pylypenko, Dmytro; Dou, WeiQiang; Yu, DeXin (Frontiers in Oncology, 2023)
Purpose: To evaluate the value of quantitative parameters derived from DKI and IVIM in differentiating histologic grades and clinical stages of ccRCC. Materials and Methods: 65 patients who were surgically and pathologically diagnosed as ccRCC were recruited in this study. In addition to routine renal magnetic resonance imaging examination, all patients underwent preoperative IVIM and DKI. The corresponding D, D*, f, MD, KA, and MK values were obtained. Independent-sample T test or Mann Whitney U test was used for comparing the differences in IVIM and DKI parameters among different histologic grades and clinical stages. The diagnostic efficacy of IVIM and DKI parameters were evaluated by ROC curve. Spearman correlation analysis was used to separately analyze the correlation of each parameter with histologic grades and stages of ccRCC. Results: The D and MD values were significantly higher in low grade ccRCC than in high grade ccRCC (all P<0.001), and in low stage than in high stage (all P<0.05), and the f value of high stage were lower than low stage ccRCC(P=0.007). The KA and MK values were significantly higher in low grade than high grade ccRCC (P=0.000, 0.000), and in low stage than high stage (P=0.000, 0.000). The AUC of D, D*, f, MD, KA, MK, DKI, IVIM+DKI values were 0.825, 0.598, 0.626, 0.792, 0.750, 0.754, 0.803 and 0.857 in grading ccRCC; and those were 0.837, 0.719, 0.710, 0.787, 0.796, 0.784, 0.864, 0.823 and 0.916 in staging ccRCC, respectively. The AUC of IVIM was 0.913 in staging ccRCC. The D, D* and MD values were negatively correlated with the histologic grades and clinical stages (all P <0.05), and the KA and MK values showed positive correlation with histologic grades and clinical stages (all P <0.05). The f value was also negatively correlated with the ccRCC clinical stage (P=0.008). Conclusions: Both the IVIM and DKI values can be used preoperatively to predict the degree of histologic grades and stages in ccRCC, the D and MD values have better diagnostic performance in the grading and staging. Also, further slightly enhanced diagnostic efficacy was observed in the model with combined IVIM and DKI parameters.